Cites and the African elephant: examining domestic implementation in Tanzania and South Africa - Bakta, Seraphina (Centre for Law and Society, 2026)
This dissertation examines the regulation of the international trade in the African elephant (AE) with a view to assessing the manner and extent to which domestic legislation in the selected countries is consistent or at variance with the Convention on International Trade in Endangered Species of wild Fauna and Flora (CITES). The study seeks to assess the listing criteria and other mechanisms for regulating such trade by examining the international regime. under CITES. Furthermore, by focusing on administrative and legislative measures, it also analyses the extent to which such measures are relevant in addressing pertinent issues concerning the African elephant. These issues include the efficacy of administrative and legislative measures in regulating international trade in the AE, the effect of CITES in the domestic regime and challenges facing effective domestic implementation in as far as the AE is concerned. The study argues that the efficacy of CITES cannot fully be realised in the absence of workable domestic regimes among member states. Both Tanzania and South Africa have made attempts to implement CITES, yet such attempts fall short of CITES and the guidelines (Annex 'D') produced by the CITES Secretariat. The study found that domestic implementation of CITES in the two countries is insufficient (and in some aspects weak) owing to various challenges. These challenges include (but are not limited to) the conflicting interests of parties, inherent weaknesses under CITES, the lack of sufficient resources, including financial constraints and technological barriers. In addition, the administrative and legislative measures adopted by the Conference of the Parties (CoPs) have not been meaningfully complied with by the two countries. The study concludes that, adequate domestic legislation should be put in place in Tanzania and South Africa in order to realise the present and future benefits of the African Elephant. To be effective however, efficacy of such legislation is whittled down in the absence of a political will.